Pelatihan Penggunaan Alat Ukur Dasar Fisika di SMK Islam Nurul Jadid Kecamatan Camplong Kabupaten Sampang - Joni, Idon; Larasati, Citra; Dewi, Nidian Puspa; Hafsi, Ainur Rofiq (Alamtana: Jurnal Pengabdian Masyarakat UNW Mataram, 2025)
Physics is actively involved in various experimental activities, particularly in observation and measurement. The purpose of this activity is to enhance students' knowledge and skills in understanding the concepts of Physics and to support the achievement of the current curriculum. Tenth-grade students in secondary school are taking theoretical physics lessons, which include the aspect of measurement. To improve students' understanding of measurement, it's best to conduct practical activities where they measure directly using basic measuring tools such as calipers, screw micrometers, multimeters, and O'haus balances. Community service at SMK Islam Nurul Jadid in Camplong District, Sampang Regency, was conducted by a team of lecturers from Madura University through training on the use of basic physics measuring instruments, with a total of 39 student participants divided into 8 groups. The results of this activity show that students' understanding and skills in using basic measuring tools have improved. This increase is based on the students' ability to take their own measurements. This is evidenced by an average assessment score of 92.7, which indicates that the criteria are of very good quality.